2006
DOI: 10.1111/j.1524-4725.2005.31154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intense Pulsed Light and the 1,064 nm Nd:YAG Laser on Sun-Damaged Human Skin: Histologic and Immunohistochemical Analysis

Abstract: Both the IPL and 1,064 nm Nd:YAG laser-induced heat activation of superficial dermal dendritic cells resulted in deposition of collagen in the papillary dermis without evident morphologic damage to the epidermis or dermis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 12 publications
0
54
3
2
Order By: Relevance
“…A recent study evaluated the action of IPL on stimulating the proliferation of collagen in human skin damaged by sun and concluded that, in addition to collagen deposition, the clinical improvement observed after treatment may be secondary to the reduction of perifolicullar inflammatory infiltrate [4,8]. Other reports indicate some degree of the appearance of newly formed collagen in the upper dermis after IPL treatment, thus suggesting the possibility that stimulated dermal fibroblasts are the source of this increased collagen expression [6,29].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…A recent study evaluated the action of IPL on stimulating the proliferation of collagen in human skin damaged by sun and concluded that, in addition to collagen deposition, the clinical improvement observed after treatment may be secondary to the reduction of perifolicullar inflammatory infiltrate [4,8]. Other reports indicate some degree of the appearance of newly formed collagen in the upper dermis after IPL treatment, thus suggesting the possibility that stimulated dermal fibroblasts are the source of this increased collagen expression [6,29].…”
Section: Discussionmentioning
confidence: 94%
“…It is possible to experimentally evaluate the histological effects of intense pulsed light and the intradermal injection of CO 2 into skin [2, 4,5,8]. Therefore, in the present study, our aim was to evaluate the effect of IPL and intradermic CO 2 injection on fibroblast proliferation and collagen in the skin of female Wistar rats.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that skin injury such as scarification or burn can enhance immune responses 40 and lasers can be used to induce such injuries to the skin. 39,[41][42][43] A number of investigators have explored the immune-stimulating effects of thermally-destructive lasers in treating cancer 44,45 and a recent review has been published covering this approach. 46 In addition, fractional laser devices used to enhance delivery of drugs and vaccines have been examined for their ability to alter immunologic responses in the skin to vaccines and immunotherapies.…”
Section: Potential Role Of Lasers As Vaccine Adjuvantsmentioning
confidence: 99%